Factor structure of the Student Engagement Instrument among Malaysian undergraduates - Mohammed Iman Karim,; Harris Shah Abd Hamid, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Student engagement has been known to be positively associated with academic performance, but there is no published valid measure for use among Malaysian undergraduates. This study seeks to examine the factor structure of the Student Engagement Instrument (SEI) in a Malay-sian sample. The scale was administered to 290 undergraduate students from the Faculty of Islamic Revealed Knowledge and Human Sciences as well as the Faculty of Economics and Management Sciences of the International Islamic University of Malaysia. Principal axis fac-tor with Promax rotation was used in exploratory factor analysis (EFA) and revealed a six-factor solution that was consistent with the factor structure found in the original study. A new factor labelled belongingness which was not discussed in previous studies was also discovered, which is worth exploring.